THE ROLE OF PHRASEOLOGICAL UNITS IN LANGUAGE LEARNING - Ziyoviddinova Shohida (Лучшие интеллектуальные исследования, 2024)
Annotation: This article talks about the importance of phraseological units in language learning. It is also reported that synonymy, antonymy, and homonymy are observed in Phraseologisms, as in lexemes, and that proverbs are also considered to be related to phraseological compounds, that is, they are also a type of phraseological compounds.